Comparison of financial performance of LPD Pakraman Singapadu before and after COVID-19 - I Gusti Ngurah Bayu Danuartha Loceng; I Gusti Ngurah Putra Suryanata; Ni Made Sumarningsih (Universitas Pendidikan Nasional, 2023)
This study utilized a mixed-methods approach to evaluate the financial performance of LPD Pakraman Singapadu Village before and after the COVID-19 pandemic, specifically from July 2019 to July 2020. Quantitative data was gathered from financial documents, including income statements and balance sheets, to compare financial metrics across the two periods. Qualitative data was obtained through semi-structured interviews with key stakeholders, including LPD staff and local business owners, to gain insights into the impact of the pandemic on financial performance. Observational methods were also employed to understand the operational changes and challenges faced by the LPD during this period. Financial documents were reviewed to extract relevant financial indicators such as revenue, expenses, and profit figures, with the 2019 financial performance, which showed a profit of Rp. 477,422,463, serving as a baseline for comparison against the 2020 performance, which saw a decrease in profit to Rp. 303,884,859 due to the pandemic's onset in March 2020. Interviews were recorded and transcribed verbatim, followed by thematic analysis to identify key themes related to the pandemic's impact on financial performance and business operations. Observations provided additional context to the quantitative data, highlighting how the pandemic influenced operational dynamics and financial outcomes. All collected data was analyzed using appropriate statistical and thematic techniques to ensure the robustness and reliability of the findings, enabling a thorough examination of the changes in the financial performance of LPD Pakraman Singapadu Village in the context of the COVID-19 pandemic.